ANALISIS KINERJA GURU GEOGRAFI SMA NEGERI SE KABUPATEN KUANTAN SINGINGI PROVINSI RIAU - Muhammad Hafiz; Rahmanelli Rahmanelli (JURUSAN GEOGRAFI FIS UNP, 2021)
This study aims to analyze: 1) Achievement of geography teachers in state high schools in Kuantan Singingi Regency 2) Self-development of state high school teachers in Kuantan Singingi 3) Performance of geography teachers in state high schools in Kuantan Singingi Regency. This type of research is descriptive with a quantitative approach. The population of this study is the geography teacher of state high schools in Kuantan Singingi Regency, Riau Province. The total population of this study was 19 teachers. Data collection using questionnaires and documentation. The results of this study found that 1) Self-development of Geography teachers in State High Schools in Kuantan Singingi Regency is still relatively low with a percentage of 25% 2) Achievement of Geography teachers in State High Schools in Kuantan Singingi Regency of Riau Province is still classified as moderate with a percentage of 74.3% 3) Levels The performance of Geography teachers in State High Schools in Kuantan Singingi Regency, Riau Province is still classified as moderate. This is based on analysis and combined percentage of self-development and achievement of Geography teachers in State High Schools in Kuantan Singingi Regency, Riau Province that the percentage of teacher performance levels is 49.68%.